MODEL-MODEL PEMBELAJARAN INOVATIF - Abdul Rahman Tibahary; Muliana Muliana (Scolae: Journal of Pedagogy, 2018)
Starting from the assumption that an educator-centered approach has many weaknesses. Meanwhile, the student-centered approach, the role of the teacher is to help students find facts, concepts, or principles for themselves. Therefore, to refer to learning efforts towards the formation of creative, interactive, innovative and inspiring student characters in the classroom learning process, the implementation of innovative based learning models is required. It is time for teachers to implement student-centered learning models as one of the learning innovations that make students the center of education. Innovative learning models are expected to enable students to develop their potential, and their ability to develop society, nation and country.